Introducing article numbering to African Scientific Reports - Nigerian Society of Physical Sciences (African Scientific Reports)
From the January 2023 issue, African Scientific Reports will use article numbers inplaceof the traditional method of continuous pagination through the volume. This step helps us to maintain a rapid, efficient production process by being able to define pagination as soon as a paper is accepted.